Alpha-enolase (ENO1) controls alpha v/beta 3 integrin expression and regulates pancreatic cancer adhesion, invasion, and metastasis. Issue 1 (December 2017) - Principe, Moitza; Borgoni, Simone; Cascione, Mariafrancesca; Chattaragada, Michelle; Ferri-Borgogno, Sammy; Capello, Michela; Bulfamante, Sara; Chapelle, Jennifer; Di Modugno, Francesca; Defilippi, Paola; Nisticò, Paola; Cappello, Paola; et al.
Abstract Background We have previously shown that in pancreatic ductal adenocarcinoma (PDA) cells, the glycolytic enzyme alpha-enolase (ENO1) also acts as a plasminogen receptor and promotes invasion and metastasis formation. Moreover, ENO1 silencing in PDA cells induces oxidative stress, senescence and profoundly modifies PDA cell metabolism. Although anti-ENO1 antibody inhibits PDA cell migration and invasion, little is known about the role of ENO1 in regulating cell-cell and cell-matrix contacts. We therefore investigated the effect of ENO1 silencing on the modulation of cell morphology, adhesion to matrix substrates, cell invasiveness, and metastatic ability. Methods The membrane and cytoskeleton modifications that occurred in ENO1-silenced (shENO1) PDA cells were investigated by a combination of confocal microscopy and atomic force microscopy (AFM). The effect of ENO1 silencing was then evaluated by phenotypic and functional experiments to identify the role of ENO1 in adhesion, migration, and invasion, as well as in senescence and apoptosis. The experimental results were then validated in a mouse model. Results We observed a significant increase in the roughness of the cell membrane due to ENO1 silencing, a feature associated with an impaired ability to migrate and invade, along with a significant downregulation of proteins involved in cell-cell and cell-matrix adhesion, including alpha v/beta 3 integrin in shENO1 PDA cells. These changes impaired the ability of shENO1 cells to adhere to Collagen I and IV and Fibronectin and caused an increase in RGD-independent adhesion to vitronectin (VN) via urokinase plasminogen activator receptor (uPAR). Binding of uPAR to VN triggers integrin-mediated signals, which result in ERK1-2 and RAC activation, accumulation of ROS, and senescence. In shENO1 cancer cells, the use of an anti-uPAR antibody caused significant reduction of ROS production and senescence. Overall, a decrease of in vitro and in vivo cell migration and invasion of shENO1 PDA cells was observed. Conclusion These data demonstrate that ENO1 promotes PDA survival, migration, and metastasis through cooperation with integrins and uPAR.